Moving the Signpost: Good Governance and Development in the Context of Public Access to Information - Corneliu Bjola (Romanian Journal of European Affairs, 2002)
In both economic and political terms, Romania lags behind most of the CEE developing countries. This situation deteriorates on a constant basis and is largely accounted for by very poor governance practices. The solution proposed by this study consists of recommending the implementation of a reformist agenda of e-governance based on two pillars: robust development of public sector information and large-scale application of Information and Communication Technologies. In conceptual terms, this strategy is assumed to produce a gradual shift from the citizen-as-customer to the more participative citizen-as-shareholder model of governance. In concrete terms, the medium-term benefits of this policy are political (enhancing the democratization process, increasing political accountability, and improving the tattered government-citizen relationship), economic (combating corruption, creating a transparent and competitive economic environment, and speeding up standard administrative processes for citizens and business), and social (restoring public trust, rebuilding social capital, and increasing the transparency, quality and efficiency of public services).